Succession Planning And Its Impact For Smmes In The Construction Industry (Journal of Namibian Studies : History Politics Culture, 2024)
Lack of a succession plan can be harmful when senior executives leave an organisation, either voluntarily or involuntarily, leaving other members exposed. For SMMEs, succession planning is still a crucial corporate governance concern. Typically, technically orientated employees work in a field where accuracy and in-depth knowledge are crucial own building companies. In this kind of industry, a lack of succession planning can result in a company failing, a rise in crime and unemployment, social unrest, and structural inequality. Twelve construction companies' business owners and executives participated in in-depth, semi-structured interviews as part of a qualitative research approach that was used to gather data. Software from Atlas.ti was used. The research highlights the need for more formalised and organised strategic succession planning efforts, whereas the findings observed that business founders are primarily focused on corporate expansion and profit maximisation. The conclusion of this article is that entrepreneurs who perceive succession planning as having negative implications related to estate planning may find it difficult to gain support from the leadership. The need for greater effort to implement training and skill development programs, organisational goals that are not in line with succession plans, and the incapacity to pursue succession plans that are in line with corporate culture are other variables that have a negative impact on succession planning initiatives.